Pengaruh Media Sosial Terhadap Minat Kunjung Wisatawan di Toraja Utara - Risaldy Adikaputra Jacob; Randi Tangdialla; Stefani Marina Palimbong (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
The Influence of Social Media on Tourist Interest in North Toraja. The purpose of this research is to determine whether social media has an impact on tourist interest in North Toraja. Data collection techniques in this study include documentation, observation, and questionnaires. The population in this research consists of tourists visiting tourist attractions in North Toraja, with a sample size of 85 respondents. The data analysis technique used is a simple linear regression test. The results of partial testing (t-test) indicate that the social media variable has an influence on tourist interest in North Toraja.